Complete Genome Sequence of the Highly Virulent Aeromonas schubertii Strain WL1483, Isolated from Diseased Snakehead Fish (Channa argus) in China - Liu, Lihui (Genome Announc, 2016)
We sequenced the complete genome of the highly virulent Aeromonas schubertii strain WL1483, which was isolated from diseased snakehead fish (Channa argus) in China. The full genome sequence of A. schubertii WL1483 is 4,400,034 bp, which encodes 4,376 proteins and contains 195 predicted RNA genes.